2023
DOI: 10.3390/agronomy13041103
|View full text |Cite
|
Sign up to set email alerts
|

Design and Test of Peanut Root-Disk Full-Feeding Longitudinal Axial Flow Pod-Picking Device

Abstract: To improve the pod-picking efficiency of the combine harvester for both peanut seedlings and peanuts, a longitudinal axial flow pod-picking device is designed in this study. The fixation and adjustment modes of the pod-picking rod were determined. The pod-picking roller’s rotational speed, the pod-picking roller’s diameter, the pod-picking roller, the pod-picking roller’s effective rod-picking length, and the screw-feeding stirrer’s critical parameters were determined by theoretical calculation. A combined des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It was found that the minimum slot length (i.e., the fertilizer flow gap) between two circular-arc fertilizer dischargers has the most significant impact on the stability CV of fertilizer discharge, and its uniformity was greatly improved, which is consistent with the conclusion made in this paper that the FGPB is an important influencing factor on fertilizer-discharge performance. Liu et al [32] designed a spiral cone centrifugal fertilizer discharger, which adopts a spiral disturbance cup structure, aiming to accelerate the flow speed of fertilizer and prevent blockage caused by the formation of fertilizer bridge arches. An experiment showed that its fertilizer stability coefficient was greater than 96%, and the CV was less than 5.57%.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the minimum slot length (i.e., the fertilizer flow gap) between two circular-arc fertilizer dischargers has the most significant impact on the stability CV of fertilizer discharge, and its uniformity was greatly improved, which is consistent with the conclusion made in this paper that the FGPB is an important influencing factor on fertilizer-discharge performance. Liu et al [32] designed a spiral cone centrifugal fertilizer discharger, which adopts a spiral disturbance cup structure, aiming to accelerate the flow speed of fertilizer and prevent blockage caused by the formation of fertilizer bridge arches. An experiment showed that its fertilizer stability coefficient was greater than 96%, and the CV was less than 5.57%.…”
Section: Discussionmentioning
confidence: 99%